Rare Metastasis of Gastric Cancer to the Thyroid Gland: A Case Report and Review of Literature - Wu, Zehui; Guo, Tao; Li, Qiang; Cheng, Liang; Hu, Xiaosi; Xu, Aman (Frontiers in Surgery, 2021)
Background: It is common for patients with gastric cancer to develop distant metastases in the liver, lung, bone, and brain. Although the thyroid also has an abundant blood supply, gastric cancer metastasis to the thyroid is uncommon. Due to the rarity of such metastasis, its clinical features are not well understood. Here, we present the case of a patient with gastric cancer metastasis to the thyroid treated at our hospital. Case Summary: We report the case of a 63-year-old female with a mass in the anterior neck and mild hoarseness for 6 months. The patient underwent proximal subtotal gastrectomy for Siewert III oesophagogastric junction cancer 6 years ago. Subsequently, she received 8 cycles of adjuvant chemotherapy. Her condition was stable until mild hoarseness developed for no apparent reason 6 months prior to presenting at our clinic. Both ultrasonography and computed tomography confirmed a heterogeneous mass in the right lobe of the thyroid gland. Blood thyroid function tests and tumor marker expression levels were normal. Thyroid malignancy was suspected, and the patient underwent a right thyroidectomy. During the surgery, a tumor was found that had invaded the right recurrent laryngeal nerve and trachea. H&E staining and immunohistochemistry results suggested that the cancer cells originated from gastric cancer. The patient was diagnosed with thyroid metastasis of gastric cancer. She refused further treatment and died within 6 months. Conclusion: Metastasis of gastric cancer to the thyroid is rare and is associated with a poor prognosis. Immunohistochemical diagnosis is essential for a conclusive diagnosis. For patients with a history of malignant tumors, the possibility of metastatic thyroid nodules should be ruled out when diagnosing thyroid nodules.